Lantibiotic production is a burden for the producing staphylococci - Ebner, Patrick (Sci Rep, 2018)
Lantibiotics are antimicrobial peptides that contain non-proteinogenic amino acids lanthionine and 3-methyllanthionine and are produced by Gram-positive bacteria. Here we addressed the pros and cons of lantibiotic production for its producing strains. Two staphylococcal strains, S. gallinarum Tü3928 and S. epidermidis Tü3298 producing gallidermin and epidermin respectively were selected. In each of these parental strains, the structural genes gdmA and epiA were deleted; all the other biosynthetic genes including the immunity genes were left intact. Comparative analysis of the lantibiotic-producing strains with their non-producing mutants revealed that lantibiotic production is a burden for the cells. The production affected growth, caused release of ATP, lipids and increased the excretion of cytoplasmic proteins (ECP). The epidermin and gallidermin immunity genes were insufficient to protect the cells from their own product. Co-cultivation studies showed that the ΔgdmA mutant has an advantage over the parental strain; the latter was outcompeted. On the one hand, the production of staphylococcal lantibiotics is beneficial by suppressing competitors, but on the other hand they impose a burden on the producing-strains when they accumulate in higher amounts. Our observations explain why antibiotic-producing strains occur as a minority on our skin and other ecological niches, but retain corresponding antibiotic resistance.